Synthesis, antimalarial activities of secondary amine-substituted eugenol compounds against plasmodium falciparum and in silico molecular docking analysis - Syahri, Jufrizal; Hilma, Rahmiwati; Nurlaili,; Sari, Meidita Kemala; Frimayanti, Neni; Amatul Hamizah Ali,; Jalifah Latip, (Penerbit Universiti Kebangsaan Malaysia, 2023)
Multi-resistance cases with antimalarial drugs had been developed in over the years. One of the ways of developing antimalarial drugs is to focus on searching for the potential antifolate inhibitors against Plasmodium sp. from synthetic or natural products. The aims of this research was to synthesis secondary amine-substituted eugenol compounds through the Mannich reaction for antimalarial evaluation using Plasmodium falciparum 3D7. The compounds were also evaluated on Plasmodium falciparum dihydrofolate reductase-thymidylate synthase (PfDHFR-TS) as a protein target and the compounds’ drug-likeness properties were determined. Five secondary amine-substituted eugenol compounds (1a-e) were synthesized via substitution of the secondary amine i.e., pyrrolidine, piperidine, methyl piperidine, and morpholine in the eugenol structures. The plasmodium lactate dehydrogenase assay (pLDH) showed that 1a and 1c had good antimalarial effects against P. falciparum 3D7 with the IC50s values of 0.89 µM and 0.62 µM, respectively. The molecular docking analysis showed that 1a and 1c had perfect interaction with PfDHFR-TS (PDB ID: 1J3I) with strong hydrogen bond interactions occurring with PfDHFR-TS protein. The eugenol derivatives 1a and 1c exerted CDOCKER binding energies of -6.1407 and -6.6536 kcal/mol, respectively. Based on this research, it was found that PfDHFR-TS is a plausible protein target for the synthesized secondary amine-substituted eugenol in P. falciparum infection. The substitution of a secondary amine group for eugenol significantly enhanced the antimalarial properties of the compounds. Thus, eugenol derivatives are potential compounds to be pursued to combat folate resistance in malarial infection.